Body composition analysis in late-onset Pompe disease. - Papadimas, G K; Terzis, G.; Methenitis, S; Spengos, K.; Papadopoulos, C.; Vassilopoulou, S.; Kavouras, S; Michelakakis, H; Manta, P (Mol Genet Metab, 2011)
Pompe disease is an inherited metabolic disorder caused by α-glycosidase deficiency. The adult onset form is mainly characterized by progressive proximal muscle weakness and respiratory dysfunction. The aim of the present study is to evaluate body composition in adult patients before and after enzyme replacement therapy (ERT). Body composition was examined at baseline by means of dual x-ray absorptiometry (DXA) in nine adult patients and after different time periods in six of them who received ERT. Total BMD (bone mineral density) was initially mildly decreased in two patients, while femoral neck BMD was decreased in five patients. On the other hand fat mass was increased in the majority of patients, while body mass index (BMI) was high in four. ERT administration did not seem to induce obvious BMD changes in any patient. Conclusively, the greater femoral neck BMD involvement may be attributed to the lower mechanical load applied by the selectively weakened muscles, whereas the increased fat mass may be the result of metabolic and nutritional derangement.
Keywords: Absorptiometry, Photon; Adolescent; Adult; Aged; Body Composition; Bone Density; Female; Femur Neck; Glycogen Storage Disease Type II; Humans; Male; Middle Aged; Young Adult